Educational environment of teachers: University = Środowisko edukacji nauczyciela: uniwersytet - Kabat, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The intellectual atmosphere of teachers' education, who get it at the centuriesold institution - university, has been presented in the article. The architecture of university encourages getting higher education, but it must undergo transformations depending on the needs and expectations of the external reality. Selected nuances of the mutual relations between university, its organization, urban shape and the teachers' education taking place there, which together form a unique environment, have been shown in the text. This environment, however, requires specific modernization, which the author has attempted to highlight selectively. The whole of the considerations have been summed up.
Keywords: uniwersytet; środowisko; kreatywność; atmosfera edukacyjna; university; teacher; environment; educational atmosphere; creativity